The Higher Education Department - Missions and Visions - Shuib, Munir (National Higher Education Research Institute, Universiti Sains Malaysia, 2003)
IPPTN recently had a rare privilege of interviewing the Director of the Higber Education Department, Y. Bhg. Dato' Professor Dr. Hassan Said, to find out the department's missions and visions. Y. Bhg. Data' Professor Hassan talked about what he aspired his department to achieve and also gave his candid comments on the challenges faced by his department and how he seeks to overcome them. The following is a brief report of the interview.